High-Quality Screening of Pharmacological Chaperones for Enzyme Enhancement Therapy - Shanmuganathan, Meera (My University, 2015)
Enzyme enhancement therapy based on pharmacological chaperones (PCs) represents a promising new therapeutic strategy for the treatment of rare genetic disorders associated with protein misfolding. PCs are small extrinsic molecules that activate, stabilize and promote folding as a way to rescue mutant enzymes from endoplasmic reticulum-associated protein degradation. To date, high throughput drug screening has relied on fluorescence-based inhibition and/or thermal stability assays for putative PC selection from large chemical libraries with confirmatory testing on patient-derived cell-based assays or animal models. However, conventional primary screening methods do not directly measure for chaperone activity that may contribute to high attrition rates in drug discovery. The major aim of this thesis is to develop and validate a high quality screening strategy for the discovery of novel PCs that restore the activity of denatured/mutant enzymes associated with Gaucher disease (GD) and phenylketonuria (PKU). Chapter II introduces a simple yet selective capillary electrophoresis (CE)-based inhibition assay for improved characterization of previously-approved FDA drugs that function as putative PCs for β-glucocerebrosidase (GCase), a lysosomal enzyme associated with GD. A novel in-vitro assay based on restoration of enzyme activity via denaturation (READ) was developed in Chapter III for unambiguous characterization of the chaperone activity of previously identified PCs for GCase when using CE with UV detection. Chapter IV subsequently adapted READ to a fluorescence-based high throughput screening platform to discover novel stilbene derivatives as PCs from a chemical library comprising structural unique compounds after in silico assessment of drug-like activity. Chapter V then used this two-tiered screening strategy to discover plant-derived natural products that enhance the activity of phenylalanine hydroxylase (PAH), the enzyme associated with PKU. In summary, an integrated two-tiered strategy for high quality screening of PCs has been developed in this thesis, which is anticipated to enhance drug discovery while reducing false discoveries for treatment of various human diseases associated with deleterious protein misfolding.
Keywords: Pharamacological Chaperones, Genetic Disorders